1997
DOI: 10.1038/sj.bjp.0701203
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of endothelium‐dependent but not of endothelium‐independent dilatation in guinea‐pig aorta rings incubated in the presence of elevated glucose

Abstract: 1 Purine compounds such as ATP and adenosine, respectively endothelium-dependent and -independent vasodilators, are largely involved in the control of vascular tone and vascular reactivity to contracting stimuli. We investigated the relaxing activity of ATP and adenosine in guinea-pig aorta rings exposed for 6 h to elevated glucose concentration (50 mM), in order to mimic hyperglycaemic conditions. Guinea-pigs were reserpine-treated (2 mg kg 71 , i.p., 48 and 24 h before death). 2 Rings of aortae incubated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
2
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 45 publications
5
21
2
2
Order By: Relevance
“…Furthermore, 1 week after introduction of insulin treatment glycaemia was below normal values but endothelial dysfunction was still present. These results disagree with studies reporting an impairment of endothelial function in vessels from non-diabetic animals incubated in very high concentrations of glucose (20 to 50 mmol/l) [18,19,20,21,22,23,24]. Nevertheless, in agreement with our findings, other authors have reported a good preservation of endothelial relaxations in short-term diabetes (1 week) induced by streptozotocin in rats [53], or after subacute (1 day) hyperglycaemia in humans [54].…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Furthermore, 1 week after introduction of insulin treatment glycaemia was below normal values but endothelial dysfunction was still present. These results disagree with studies reporting an impairment of endothelial function in vessels from non-diabetic animals incubated in very high concentrations of glucose (20 to 50 mmol/l) [18,19,20,21,22,23,24]. Nevertheless, in agreement with our findings, other authors have reported a good preservation of endothelial relaxations in short-term diabetes (1 week) induced by streptozotocin in rats [53], or after subacute (1 day) hyperglycaemia in humans [54].…”
Section: Discussioncontrasting
confidence: 57%
“…Some authors indicate that increased glucose itself is a source of free radicals that leads to endothelium dysfunction [18,19,20,21,22,23,24]. Our results, however, clearly indicate that high glucose by itself is not directly related to the impairment of endothelium-dependent relaxations.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In some other vascular tissues, effects to short-term glucose exposure are similar to those of diabetes. Thus, in rabbit and guinea pig aorta, high glucose effects are linked to ROS-stimulated endothelial release of a prostanoid vasoconstrictor which opposes ACh-induced relaxation [59,60]. A similar effect was noted for rat mesenteric resistance vessels, combined with depression of endothelium derived hyperpolarising factor mediated responses [61].…”
Section: Discussionmentioning
confidence: 68%
“…Хоча збільшення часу інку-бації до 6 год призводило до зниження ендотелійзалежної дилатації і у судинних сег-ментів грудної аорти самців [16,39]. При цьому ендотелійнезалежна вазодилатація (Na-нітропрусид, A23187) не зазнавала змін після 6 год інкубації за високих концен-трацій глюкози (44 мМ, 50 мМ) сегмен тів аорти як щурів, так і мурчаків обох статей [12,39].…”
Section: рисunclassified